Associations between metabolic syndrome and gynecologic cancer - Da Yong Lee; Taek Sang Lee (Korean Society of Obstetrics and Gynecology, 2020)
Metabolic syndrome (MetS) is a group of risk factors that causes cardiovascular and diabetic morbidity and mortality, which is diagnosed by central obesity, dyslipidemia, hyperglycemia, and hypertension. Increasing epidemiological data and experimental results indicate that the presence of MetS increases the incidence of common malignancies and related mortality. Epidemiological studies have previously reported an association of endometrial cancer occurrence with MetS. Aromatization of androstenedione to estrogen, insulin resistance, and diabetes can cause increased levels of free estrogen, and the detrimental effect of elevated estrogen as a carcinogen is well studied in endometrial cancer. Medications used to manage MetS such as metformin and statins are suggested to reduce endometrial cancer risk and improve survival. Some large population-based epidemiological studies have suggested that the MetS is related to an increased risk of cervical carcinoma. MetS may contribute to viral-host interactions, which lead to persistent human papilloma virus (HPV) infection, although limited epidemiological data are available. Specific effects of obesity and diabetes on the occurrence of ovarian cancer have been suggested. However, the direct correlation between MetS and ovarian cancer is still lacking. Previous retrospective studies reported that the use of metformin, statins, and beta-blockers could be associated with cancer prevention or better prognosis. Proper diagnosis and management of the MetS should be a part of the strategies undertaken to prevent and treat gynecologic cancer. So far, only limited data is available on this subject, and further clinical and fundamental research is required to further clarify the effect of these therapies on gynecologic cancer treatment.